Malaysia, Singapore & Brunei - Albiston, Isabel; Atkinson, Brett; Benchwick, Greg; Bonetto, Cristian; Bush, Austin; Isalska, Anita; Kelly, Robert Scott; Richmond, Simon; Waters, Richard ([Footscray, Victoria] : Lonely Planet, 2016)
Southeast Asia's terrific trio offer steamy jungles packed with wildlife, beautiful beaches, idyllic islands, culinary sensations and multi-ethnic culture.
Plan your trip -- On the road -- Understand Malaysia, Singapore & Brunei -- Survival guide.
Includes bibliographical references and index.
Keywords: Travel; Malaysia -- Guidebooks; Malaysia -- Description and travel; Singapore -- Guidebooks; Singapore -- Description and travel; Brunei -- Guidebooks; Brunei -- Description and travel; Brunei; Malaysia; Singapore; Guidebooks